Bridging the gap: Unveiling assessment literacy among non-formal education tutors - Elih Sudiapermana; Yanti Shantini; Nike Kamarubiani; Witri Dian Rafani (LPMPP Universitas Negeri Yogyakarta, 2026)
Although assessment literacy is increasingly recognized as a critical component of effective teaching, empirical research addressing this competency in non-formal education contexts remains limited. This study addresses this gap by examining the level and distribution of assessment literacy among non-formal education (NFE) tutors in Indonesia and by exploring the structural validity of an assessment literacy framework adapted to non-formal learning environments. Using survey data collected from 322 NFE tutors, the study investigates variations in assessment literacy across demographic and professional characteristics and analyzes the contribution of seven conceptual dimensions to overall assessment literacy. The findings indicate that tutors’ assessment literacy levels are generally modest. No significant differences are observed in relation to gender, length of teaching experience, or type of educational work experience, whereas age and educational attainment are associated with statistically significant variation. All seven dimensions demonstrate meaningful relationships with assessment literacy, with contextual responsiveness and reflective practice emerging as particularly influential, while several indicators require further refinement. By providing empirical evidence on assessment literacy in non-formal education settings, this study contributes to the refinement of existing conceptual frameworks and underscores the importance of context-sensitive professional development and institutional support in enhancing assessment practices and learning quality in non-formal education.